Qadhaya al-Mar’ah al-Ijtima’iyah al-Haditsah ‘Inda Zainab Al-Ghazali Fi Tafsiriha “Nazharat Fi Kitabillah” - Rochmad, IIUM; Khaled, Nashwan Abdo (2020)
Abstract Zainab Muhammad Al-Ghazali was one of the greatest women who had a real contribution to the modern interpretation of the Holy Quran to overcome the whole Islamic civilization’s problems. Her masterpiece “Nadzarat Fi Kitabillah” is becoming one of the important references in this century and included as the social interpretation book. This magnum opus of Zainab Al-Ghazali has several advantages that are focused on social problems, in particular, the role of women and family issues in this modern era in the Quran with the clear explanations and sample. Moreover, the work of Zainab Al-Ghazali was supported by elements of bil ma’tsur which are revealing the meaning of the Quran by Quran, and by Hadits of the Prophet Muhammad Peace Be Upon Him, also by the explanation of companions. This research focused on four famous issues among women which are the witnesseth of women, polygamy, inheritance and the men leadership over women, inductive and analytical method that will be adopted. This inquiry has the same important results, First, oblivion is the biggest cause of the testimony of the two women is equivalent to the testimony of a man. Secondly, in the case of polygamy, Zainab refers to the majority opinion of the scholars and advises women to be the best partner in life. Third, the inheritance right in a woman according to of Zainab Al-Ghazali perception is determined by God. Fourthly, the meaning of qawamah is the responsibility to fill all material needs and to be a good partner for his family.